The effect of different protease inhibitors on stability of parathyroid hormone, insulin, and prolactin levels under different lag times and storage conditions until analysis - HAKLAR, GONCAGÜL; ŞİRİKÇİ, ÖNDER (WILEY, 2017)
IntroductionProteolytic cleavage through proteases affects peptide hormone levels, which is of particular significance when the time interval between sampling and analysis is prolonged. We evaluated the stability of parathyroid hormone, insulin, and prolactin molecules (i) with different protease inhibitors such as K(2)EDTA, aprotinin, and protease inhibitor cocktail (PIC), (ii) with different lag times (6-72hours), and (iii) under different storage temperatures (4 degrees C vs room temperature [RT]) until analysis. Materials and MethodsBlood samples were collected into 2 sets of 5 Vacutainer((R)) tubes (Becton Dickinson) from 10 healthy adults. Tubes 1 and 2 were plain gel separator tubes. Tubes 3, 4, and 5 contained PIC (1%), aprotinin (500 KIU/mL), and K(2)EDTA, respectively. After centrifugation at 1300g for 10minutes, PIC added to tube 2 of each set. Samples were analyzed and then one set was stored at 4 degrees C, whereas the other at RT until analysis at 6, 24, 48, and 72hours. Hormone levels were determined with electrochemiluminescence immunoassay (ModularE170; Roche Diagnostics). The results were compared with desirable bias limits (DBL) from Westgard QC database. ResultsInsulin at RT decreases exceeding the DBL starting from 24hours and K(2)EDTA preserved insulin. PTH exceeded the DBL at RT for 48hours or longer and PIC addition after centrifugation inhibited its degradation. Prolactin remained stable in all tested conditions. All parameters in the plain gel separator tubes remained within DBL when stored at 4 degrees C until 72hours. ConclusionsDifferent proteases may degrade peptide hormones and measures should be taken to counteract these effects especially if there is a delay before analysis.
Keywords: insulin; parathyroid hormone; pre-analytical phase; prolactin; protease inhibitors